Religious Leaders and Organ Donation – an Indian Experience. (August 2017) - Raghuram, Lalitha; Shroff, Sunil
Abstract : Introduction: India is a land of multiple religions and this impacts socio-cultural attitudes and practices. In the two decades of its existence, MOHAN Foundation has engaged with several religious/spiritual leaders for perspectives on organ donation. We studied the results of our work with one spiritual guru and whether it led to actual donations from his followers. Methods: On December 3rd, 2012, MOHAN Foundation organized a "one of its kind" multi-religious confluence titled "Sant Sangama". In this Confluence, all religious leaders unanimously endorsed organ donation as the most supreme form of gift. One of the globally renowned Hindu religious leaders is Sri Sri Sri Tridandi Chinna Jeeyar Swamiji, who has over 3 million followers across the world. MOHAN Foundation has been in close contact with him and his followers since mid 2013. He endorsed organ donation quoting the Hindu scriptures, which was made into a film. Following this, several events like (i) organ donor families felicitation (ii) walkathon with a participation of over 15, 000 people (iii) cyclothon (iv) kiosk on organ donation outside temples in USA and Australia (v) organ donation talk during his spiritual discourses were conducted in 2014 and 2015. Totally, 22 joint events were conducted. We distributed over 15, 000 Donor Cards. Results: Between December 2013 and March 2017, we received over 50 telephone calls from the followers to donate organs of their family members. But they were not "Brain Dead". They were either dead "at the spot of the accident", were in an old age home or had had a circulatory death. When they were informed that they were unsuitable for organ donation, and then asked if they would like to donate their eyes, they readily consented. A total of 26 eye donations were made. Some of them were willing to donate the body also, but lack of infrastructure in that area was an impediment to fulfilling their wishes. Conclusion: It is observed that religious leaders endorsing the cause of organ donation creates greater awareness among followers, but that alone does not suffice when translating to actual organ donations from them. Ongoing education of followers is required to ensure understanding, acceptance and commitment to organ donation.